Beyond Tracking: The Relationship of Opportunity to Learn and Diminished Math Outcomes for U.S. High School Students. Issue 6 (June 2022) - Wronowski, Meredith L.; Thornton, Margaret; Razavi-Maleki, Bita; Witcher, Angelica W.; Duarte, Bryan J.
Background/Context: In this study, we draw on evolving definitions of opportunity to learn (OTL) to conceptualize mathematics OTL has having two main components: structural OTL, defined by gatekeeping access to specific mathematics courses through the process of tracking, and instructional OTL, defined by the learning experiences of students in their mathematics courses. We also conceptualize both of these aspects of OTL as occurring in the current educational milieu, where sociopolitical factors reward or punish specific school strategies. Purpose/Objective/Research Question/Focus of Study: This study seeks to examine, using an OTL framework, the relationship between high school math teachers' instructional practices, students' course tracks in mathematics, students' perceptions of mathematics, and students' distal measures of academic attainment, including completion of advanced math coursework and completion of a high school diploma. Research Design: Using latent class analysis, this secondary data analysis analyzed the 2009 High School Longitudinal Study data from the National Center for Educational Statistics to examine mathematics instructional OTL based on math teachers' objectives of emphasis and its relationship to structural OTL in the form of course tracking. Findings/Results: We identified "Enriched" and "Rote Knowledge and Skills" latent classes of math OTL. Teachers providing Enriched OTL emphasize the widest variety of objectives, including cognitively demanding problem-solving and logic objectives and practical applications of mathematics, while teachers providing Rote Knowledge OTL emphasize basic computation, algorithms, and computation skills. Black students, Hispanic students, and students living in poverty were more likely to be in math OTL classes focused primarily on basic concepts, algorithms, and computation, with little to no emphasis in more applied and cognitively demanding math course objectives, and they were less likely to be enrolled in advanced ninth-grade math courses. Students in Rote Knowledge OTL courses with little to no emphasis in applied and cognitively demanding math course objectives had lower mathematics identity and self-efficacy, and math achievement. Conclusions/Recommendations: This study adds to the literature suggesting that students in the United States experience an opportunity gap rather than an achievement gap, and that opportunity gaps are both structural and instructional. This study also adds to the literature suggesting student sorting systems are inherently unequal and must be addressed through policy, leadership, and cultural shifts in both schools and districts.